Early Pliocene paleoenvironment of the Sorsdal Formation, Vestfold Hills, based on diatom data - Whitehead, JM; Quilty, PG; Harwood, DM; McMinn, A (Marine Micropaleontology, 2001)
Comparison of diatom data from modern surface sediments in Prydz Bay and the Kerguelen Plateau with diatom assemblages from the Srsdal Formation, Vestfold Hills, indicates that the climate was warmer than present during the early Pliocene (4.5-4.1 Ma). Extant, sea-ice associated diatoms are significantly less abundant throughout the Srsdal Formation than in the modern Antarctic coastal zone. Extant diatoms in the Srsdal Formation, including Stellarima stellaris, Thalassiosira oliverana, Fragilariopsis sublinearis, Pseudo-nitzschia turgiduloides and Eucampia antarctica var. recta, are consistent with annual sea-surface temperatures (SST) of between - 1.8 and 5.0C. The presence of S. stellaris indicates that the summer SSTs were >3C during some intervals. The absence of calcareous coccoliths and the silicoflagellate Dictyocha suggests that the upper limit for summer SST was <5C. These data indicate that early Pliocene summer SST were between 1.6 and 3C warmer than today. Abundant Chaetoceros cysts infer that stratified, open-water conditions were present during summer/spring. Ice sheet models suggest that warming of the magnitude evident in the Srsdal Formation (3C) should have resulted initially in increased snow accumulation and ice sheet growth. However, ice sheet growth was probably short-lived, as the long-term response to this warming in the early Pliocene resulted in a significant decrease in ice volume and deposition of the Srsdal Formation. Other factors, such as increased basal-ice sliding and higher discharge (icebergs and melt-water), probably led to significantly elevated ablation rates from the Pliocene ice sheet, resulting in ice sheet retreat. 2001 Elsevier Science B.V.